(3TQM MRH GdHMQs - (3YHO Gddg Hf Ydj Hf YHO GdQMef ShjOGf GdOedjLj,J (B1234 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdefYe GdhgGH hGdUdGI hGdSdGe Ydi CMH GdCMHGH hYdi Bdg hCUMGHI GdCfLGH CeG HYO (B: (3gPG TQM dWja Ydi GdMcRH GdcHjQ ddbWH GdTGPdi s
(3BNQgG (B:s
(3Hd cd TF dMceg hEfce EdjfG dG JQLYhf Hd JYhOhf EdjfG aGOYhg eNdUjf dg GdOjf Ei GdWGYI ef GdQjGA hfMhg hGdMeO ddg QH GdYGdejf Ci bGFdjf Pdc hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHYs
(3GdMRH GdcHjQ ddTGPdi GfXQ cTa GdXfhf L(B1 (3U` (B662(3JUhas
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B107 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B89s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdeLGejYs